Is energy efficiency a robust driver for the new normal development model? A Granger causality analysis. (October 2022) - Panait, Mirela; Apostu, Simona Andreea; Vasile, Valentina; Vasile, Razvan
Abstract: The article analyzes the causal relationship between energy efficiency, calculated as a ratio between GDP/capita and PPP and CO2 emissions (tons/capita), and a range of economic and social variables that outline the performance of development. The analysis focuses on the European space and database is covering the last three decades. The results show that at the level of European countries, for the period 1990–2018, energy efficiency presents no causality with HDI, or trade openness, instead there is a bidirectional causality with FDI and a unidirectional causality with globalization index and share of renewable energy. By associating these results with national energy transition strategies and policy measures that promote energy efficiency, we conduct a contrastive analysis of national policy measures and differences, recommending a reconsideration of priorities in national policies on sustainable development by achieving the objectives of the SDGs and enhancing energy independence by increasing investment in renewable energy. Overall, this paper argues that energy efficiency should be the main driver for future economic development. Moreover, the role of energy independence based on investments in renewable energy is not only a factor in ensuring the sustainability of future economic growth, but also a factor in national security. Highlights: European countries registered an ascending trend regarding energy efficiency. There is a bidirectional causality between energy efficiency and FDI. There is unidirectional causality, from energy efficiency to globalization index. There is unidirectional causality from the share of renewable energy to energy efficiency. Implementing Green finance in the EU countries is necessary.